Impact of farmer self-identity and attitudes on participation in agri-environment schemes. (June 2020) - Cullen, Paula; Ryan, Mary; O'Donoghue, Cathal; Hynes, Stephen; hUallacháin, Daire Ó; Sheridan, Helen
Highlights: Investigation into the relationship between self-identity and attitudes towards schemes and their impact on participation. Novel use of factor and regression analysis to analyse the agri-environment scheme participation decision. Nationally representative sample of 1000 farmers with information on behaviour, attitudes, self-identity and farm and farmer characteristics. Farmers with a Forward looking self-identity are more likely to be scheme participants while the influence of the other self-identities depends on the farmers' attitudes towards schemes. Farmers are 10 times more likely to participate in schemes if all their neighbours are participants than farmers with no participant neighbours or if they do not know if they participate. Abstract: Influencing farmers to make positive contributions to the environment is one of the goals of agri-environment schemes (AESs). Understanding the drivers of farmer behaviour and the choices they make with regards to AESs is important as this aids policy makers in creating schemes that have a wider scope and are more likely to achieve environmental goals. Past studies have identified the importance of farmer self-identity and attitudes in decisions made on farms. Little emphasis has been put on modelling the relationship between self-identity and attitudes towards schemes and the resulting impact on participation in voluntary AESs. Using Ireland as a case-study, this paper employs a survey of 1000 farms to look at participation in AESs through the lens of farmer perceived self-identity and their attitudes towards schemes. A relatively novel approach of combining factor analysis, to generate a self-identity typology, with an AES participation regression model is implemented. The model results suggest that self-identity and attitudes have a significant impact on AES participation. Neighbouring farmers' viewpoints also have a significant and positive impact on the participation decision made by farmers.